Emerging Trends in the Social and Behavioral Sciences 2015
DOI: 10.1002/9781118900772.etrds0083
|View full text |Cite
|
Sign up to set email alerts
|

Divorce

Abstract: There is by now a large literature on divorce which seeks to understand the underlying reasons behind trends in divorce rates and establish the predictors of divorce as well as its consequences for adults and children. Early research examined divorce over time and across societies, and developed conceptual models to understand which factors affect partners' decisions to divorce. Recent cutting edge research has expanded on this literature and examined the multiple causes and consequences of divorce, heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Amato and James 2010) and are often more similar than one might expect (Härkönen 2015). However, many studies have reported cross-national variation in the strength of associations (e.g., Brolin Låftman 2010; Radl et al 2017, this Special Issue).…”
Section: Cross-national Variationmentioning
confidence: 93%
“…Amato and James 2010) and are often more similar than one might expect (Härkönen 2015). However, many studies have reported cross-national variation in the strength of associations (e.g., Brolin Låftman 2010; Radl et al 2017, this Special Issue).…”
Section: Cross-national Variationmentioning
confidence: 93%
“…Similar to the U.S., divorce in Europe has increased since the 1960s, levelling off since the 1980s (EUROSTAT, 2018). Several fundamental predictors of divorce (age, age at first marriage, presence of children, gender, income, and education) point in the same direction across the European continent, but the effect sizes vary within regions or specific nations (Härkönen, 2015). For instance, in a meta-analysis of studies predicting divorce risk across Europe, Wagner and Weiß (2006) find that even a well-established predictor of divorce—the presence of children—ranges in effect size from a 25% decline in the risk of divorce in Germany to a 70% decline in the Netherlands.…”
Section: Siblings and Divorce In Europementioning
confidence: 99%
“…Likewise, even the Dayak Tamambaloh Catholic Church views divorce as a very unwelcome situation and an immoral act. Divorce can be defined as an event to break or leave, and the end of the marriage bond (Härkönen, 2015). Divorce undermines commitment to marriage as a context for sexual relations and childbearing (Su, 2017).…”
Section: Inseparable/ No Divorcementioning
confidence: 99%